Dinamika Pendidikan Dasar Islam Sabilal Muhtadin Banjarmasin (1986-2019) - Meika Nurul Wahidah; Syaharuddin Syaharuddin; Melisa Prawitasari; ‪Mohamad Zaenal Arifin Anis; Heri Susanto; Herry Porda Nugroho Putro (Publikasi Berkala Pendidikan Ilmu Sosial, 2021)
The development of basic education (TK, SD, SMP) with the name "Sabilal Muhtadin" has a close relationship with the existence of the Masjid Raya Sabilal Muhtadin Banjarmasin. The people of Banjarmasin seem interested in this Islamic-based education. The existence of Sabilal Muhtadin's education becomes important when people have a high enough interest. The purpose of this study is to describe the dynamics of Islamic Primary Education of Sabilal Muhtadin Banjarmasin from 1986 to 2019. This research uses historical methods, refers to primary sources, through interviews with existing educators, as well as documents related to research topics. Continued source criticism and interpretation until the historiography stage. The results of the study show that the Sabilal Muhtadin Islamic Primary Education in Banjarmasin which consists of TK-SD-SMP is part of the education unit under the management of the Sabilal Muhtadin Islamic Education Institute (LPI-SM) Banjarmasin. Kindergarten Islam Sabilal Muhtadin was founded in 1986, SD in 1989 and SMP in 1993, its existence had become the prima donna of its time, this condition has survived until now, however, the development of Islamic basic education Sabilal Muhtadin still has competitiveness and can continue to grow despite experiencing competition with other education based on integrated Islamic education.